Neonatal outcome in new-borns admitted in NICU of tertiary care hospital in central India: a 5-year study - Verma, Jyotsna; Anand, Shweta; Kapoor, Nawal; Gedam, Sharad; Patel, Umesh (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal mortality rate contributes significantly to under five mortality rates. Data obtained from pattern of admission and outcome may uncover various aspects and may contribute and help in managing resources, infrastructure, skilled hands for better outcome in future. Methods: This retrospective study was done on 1424 neonates who were admitted at LN Medical College and JK Hospital, Bhopal in neonatal intensive care unit (NICU) in the Department of Paediatrics from January 2013-December 2017. Results: 1424 newborns admitted within 24 hours of birth were included in the study. About 767 were male neonates, (Male: female1.16:1). The low birth weight babies were 54% in our study. Among the various causes of NICU admission, Respiratory distress was present in 555 (39%) of neonates, Respiratory distress syndrome (Hyaline membrane disease) being the most common cause of respiratory distress. Neonatal sepsis accounted for morbidity in 24% of neonates, with Klebsiella being the most common organism grown in the blood culture. The incidence of congenital anomalies was 2.5%. The neonatal mortality was found to be 11% in our study. Prematurity with Respiratory distress syndrome (Hyaline membrane disease) and perinatal asphyxia were the two most common causes of neonatal mortality in the study. Extremely low birth weight neonates had the highest case fatality rate in the study, which indicates the need to develop an efficient group of professionals in teaching hospitals who will provide highly specialized and focused care to this cohort of vulnerable neonates. Conclusions: Present study has shown respiratory distress, perinatal asphyxia, and sepsis as the predominant causes of neonatal morbidity. All three are preventable causes, and our health-care programs should be directed toward addressing the risk factors in the community responsible for the development of these three morbidities. The preterm and low birth weight babies had significantly high mortality even with standard intensive care; therefore, a strong and effective antenatal program with extensive coverage of all pregnant females specifically in outreach areas should be developed which will help in decreasing preterm deliveries and also lower the incidence of low birth weight babies.